2017
DOI: 10.3390/urbansci1030027
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Noise and Socioeconomic and -Demographic Status on Cardiovascular and Respiratory Diseases on Borough Level in a Large German City State

Abstract: Worldwide, cardiovascular and respiratory diseases are increasing. Environmental noise and the socioeconomic and sociodemographic situation are important factors for the diseases. Using borough health claims data from 2011 in the city of Hamburg, ecological analyses with principal component analyses were conducted to describe the relationship of road traffic noise L den (day, evening, and night) > 65 dB(A), physician density, and social deprivation with regional prevalence rates of heart failure and hypertensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…The results of this study are in accordance with other studies, which have examined only individual determinants (e.g., arterial hypertension and quality of life). In particular, the relationship of arterial hypertension with educational status could be proven by numerous studies; higher education is often associated with lower risk of arterial hypertension [7,18,19]. Here, we found that high education status (ISCED = 3) is associated with only about half the risk of hypertension compared to low educational status (ISCED = 1).…”
Section: Discussionsupporting
confidence: 50%
“…The results of this study are in accordance with other studies, which have examined only individual determinants (e.g., arterial hypertension and quality of life). In particular, the relationship of arterial hypertension with educational status could be proven by numerous studies; higher education is often associated with lower risk of arterial hypertension [7,18,19]. Here, we found that high education status (ISCED = 3) is associated with only about half the risk of hypertension compared to low educational status (ISCED = 1).…”
Section: Discussionsupporting
confidence: 50%
“…Not only the respiratory tract is affected by air pollutants but also the cardiovascular system [45] and other organs such as the brain. Noise, especially road traffic and aircraft noise, is considered to be a relevant risk factor for adverse health effects [46]. Several studies have shown the link between noise and different cardiovascular and mental health outcomes [47].…”
Section: Living Environmentmentioning
confidence: 99%
“…It is necessary to know not only the stressors but also the locations and activities of the urban dwellers in sufficient detail. A simple way of accounting for exposure would be to use census data and combine them with maps of environmental stressors (e.g., [37,38]). However, for a comprehensive assessment of exposure, dynamic exposure models are currently developed.…”
Section: Exposure Modelsmentioning
confidence: 99%
“…The health of urban dwellers, an integral part of the target function of UrbWellth, depends on the different sectors of the urban system. The associations between different potential determinants (e.g., environmental stressors: noise, air pollution, and meteorological variables, which lead to heat stress) and health are usually simulated with statistical models (e.g., [37,38]), denoted here as health models. Regression models, in which one (univariate) or more (multivariate) independent variables are linked to a certain health outcome (i.e., dependent variable), are frequently used.…”
Section: Health Modelsmentioning
confidence: 99%